Rumen acidosis in ruminants: a review of the effects of high-concentrate diets and the potential modulatory role of rumen foam - Mao, Jinju; Wang, Lizhi (Frontiers in Veterinary Science, 2025)
This review delves into the intricate processes by which high concentrate diets (HCD) in ruminants trigger rumen acidosis, with particular attention to the initiating factors of the condition and the pivotal role of rumen foams in its progression. High concentrate diets lead to an excessive accumulation of acids within the rumen, creating a favorable environment for the formation of rumen foam. This foam exacerbates the severity of rumen acidosis, making it a more challenging condition to manage. Additionally, HCD significantly diminishes salivary secretion, which not only increases the viscosity of rumen contents but also hampers the absorption of volatile fatty acids and the release of carbon dioxide (CO₂). Moreover, the review highlights a previously underexplored mechanism: the build-up of CO₂ may play a crucial role in the pathogenesis of rumen acidosis. This oversight could have significant implications for understanding the onset and advancement of the condition. In essence, this paper seeks to establish a robust scientific framework to optimize ruminant nutrition and production practices, ultimately ensuring the health and well-being of these animals.